Analisis Finansial Pendapatan Peternak Plasma Broiler Open House System PT X di Kabupaten Kediri - Niswatin Hasanah (Politeknik Negeri Jember, 2018)
The study aimed to determine the production costs, revenue, earning, farming efisiency in terms of financial aspects. The farm efficiency can be obtained although R/C ratio, and BEP price during 6 production period of 30 plasma according to 3 scale enterprises. Birds stratum divided into stratum I (3.000â€“12.000 birds, n= 16), stratum II (12.001-21.000, n= 11), stratum III (21.001-30.000 birds, n= 3). The results indicated that the highest profit was strata III period 2 (Rp2,217.00/kg of live weight), the production cost was Rp14,700.00/kg of live weight (influenced by feed factor 75.7% and DOC 22.3%) and the revenue was Rp17,580.00 (consisted of affected by 98.8% broiler sales and bonus 0,57%) to produce 1 kilogram of live weight of broiler. In strata III period 2 the most efficient based on BEP price reached Rp15,252.00/kg broiler live weight and aspect R/C ratio was 1.17.Â